Rotten kids with bad intentions - Nick Netzer; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2010)
We examine a 'Rotten Kid' model (Becker 1974) where a player with social preferences interacts with an egoistic player. We assume that social preferences are intentionbased rather than outcome-based. In a very general multi-stage setting we show that any equilibrium must involve mutually unkind behavior of both players, endogenously generating negative emotions rather than positive altruism. In a large class of two-stage games that includes principal-agent and gift-giving games, this prevents equilibrium from being materially Pareto efficient. Compared to the subgame-perfect equilibrium without social preferences, efficiency is still generally increased. On the other hand, the materialistic player has lower whereas the reciprocal player has higher material payoffs, so that reciprocity does not increase equity: For sufficiently strong reciprocity concerns, the materialistic player ends up with a negligible share of the gains from trade.
Keywords: C72; D03; D86; J01; 330; Reciprocity; Psychological Games; Moral Hazard; Gift Giving; Eigeninteresse; Altruismus; Moral Hazard; Austauschtheorie (Soziologie); Nichtkooperatives Spiel; Prinzipal-Agent-Theorie